Regulatory measures affecting services trade and investment: Distribution, multimodal transport, and logistics services - Lai-Lynn A. B. Barcenas; Glenda T. Reyes; Jose L. Tongzon; Ramonette B. Serafica (Philippine Institute for Development Studies (PIDS), 2017)
Barriers to trade and investment stifle economic expansion. The impacts are most profound when they are applied to the services sector given its role as "the glue that binds all sectors together". This report examines the various regulatory requirements and legal obstacles that limit or discourage trade and investment in the services sector. It also assesses consistency with core obligations in new generation free trade agreements. In distribution, multimodal transport and logistics (DML) services, restrictions in the form of foreign ownership limitations, and other discriminatory measures are prevalent. In addition to the formal restrictions, burdensome requirements and inconsistent application of regulations lead to higher transactions cost. In other cases, it is the lack of regulation or weak enforcement that adds to the risks of doing business in the Philippines. To foster the development of DML services in the Philippines, barriers to trade and investment must be reduced. Improving regulatory governance, ensuring policy coherence, and strengthening policy coordination are also necessary to facilitate integration and the seamless supply of these services that are vital to the continued growth of the goods sector of the economy.
Keywords: 330; services; distribution; transportation; multimodal; logistics; trade; investment; regulations; barriers